Developing Quality Measures for Adult Cochlear Implant Centers: Preliminary Findings. (November 2016) - Vila, Peter M.; Lieu, Judith E. C.; Hullar, Timothy E.; Buchman, Craig A.
The study objective was to develop quality measures for adult cochlear implant centers. A modified Delphi design beginning with focus groups of surgeons and audiologists was used, as adapted from the American College of Cardiology / American Heart Association method for creating quality measures. Two academic cochlear implant programs and 1 private program participated. Qualitative focus group analysis yielded 58 candidate measures. An additional 5 candidate measures were added from a systematic review of the literature. After exclusion of pediatric measures, structure measures, and process measures and discussion of details and implications of each measure, 8 measures remained as the preliminary Adult Cochlear Implant Outcome (CI-OUTCOME) Measure Set. This study provides a preliminary set of measures for evaluating the quality of adult cochlear implant centers, based on input from implant surgeons and audiologists. The next step will be to gather feedback from implant patients.